The Dry Eye Disease Activity Log Study - Jayant V. Iyer; Sze-Yee Lee; Louis Tong (The Scientific World Journal)
Prolonged visually stressful activities aggravate dry eye disease (DED). The duration spent on such activities and their relationship with DED clinical features were investigated. Patients completed an activity log as they performed their usual activities over 1 typical rest day and 1 typical work day. The log included time spent in an air-conditioned environment, windy environment, driving, watching television, computer use, reading, watching a movie in the theatre, and wearing contact lens. Average daily activity hours were calculated and correlated with clinical features of DED. Thirty-five logs were returned. Positive correlation was found between watching television and episodic blurred vision (P<0.01). Computer use was negatively correlated with episodic blur vision, burning sensation, and gritty sensation (P<0.05). Negative correlation was found between time spent in windy environments, driving, reading, and certain DED symptoms (P<0.05). Reading correlated positively with severity of corneal fluorescein staining and reduced Schirmer’s values (P<0.03). The use of air conditioning correlated negatively with episodic blur vision but positively with visual blurring that improves with lubricants (P=0.02). This study is the first to evaluate the relationship between time spent on DED-aggravating activities and DED clinical features. Negative correlations between certain activities and DED symptoms suggest an unconscious modification of lifestyle to alleviate symptoms.